The superior education and the cultural patrimony - Apablaza, Fernando Pino (2019)
This manuscript is part of investigation that was done in the end of second trimesterin the year 2018, in the city of Lima. The objective was make a test in the thirdeducational level in direct relation with syllabus of Management and Conservationof Cultural Patrimony or Naturally Patrimony courses with the purpose to detectweakness for afterwards improve. The analyze considered three professional schoolsof tourism and hostelry in the province of Lima. The instrument that was used toevaluate the syllabus was made for the Education Ph.D. Mr. José Florés Barboza andadapted by the author of this article. The instrument is an ideal model of syllabus for competences, which was a pattern to compare the syllabuses which are subjects of study. The type of investigation is descriptive, also is transversal and quantitativeperspective too, with a sample of three syllabus of tourism and hostelry schools ofLima city.